2004
DOI: 10.1518/hfes.46.4.625.56814
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Based E-Mail and Driver Behavior: Effects of an In-Vehicle Message System Interface

Abstract: As mobile office technology becomes more advanced, drivers have increased opportunity to process information "on the move." Although speech-based interfaces can minimize direct interference with driving, the cognitive demands associated with such systems may still cause distraction. We studied the effects on driving performance of an in-vehicle simulated "E-mail" message system; E-mails were either system controlled or driver controlled. A high-fidelity, fixed-base driving simulator was used to test 19 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 21 publications
2
63
1
1
Order By: Relevance
“…The data analysed in this study are from a driving simulator experiment that is representative of other studies done in this area (Lee et al 2001, Jamson et al 2004 and that was conducted in part to assess the effects of driver distractions and different strategies to help mitigate them. For a complete description of the experiment, see Donmez et al (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data analysed in this study are from a driving simulator experiment that is representative of other studies done in this area (Lee et al 2001, Jamson et al 2004 and that was conducted in part to assess the effects of driver distractions and different strategies to help mitigate them. For a complete description of the experiment, see Donmez et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…This is a common test scenario used in driving simulator experiments, with a key performance measure being brake response time (Lee et al 2001, Jamson et al 2004. Brake response time is defined as the time from the lead vehicle braking to the release of the accelerator, and the transition time from the accelerator to the brake.…”
Section: Response Variable: Accelerator Release Timementioning
confidence: 99%
“…In a simulator-based task manipulating the control over in-vehicle messaging, Jamson, Westerman, Hockey, and Carsten (2004) found that while drivers were making adjustments in their headway (increasing their headway from a lead vehicle) during a distracting task, they were significantly less likely to anticipate the braking of a lead vehicle. This was reflected in the significant increases in braking reaction time.…”
Section: Reaction Timementioning
confidence: 99%
“…IVIS can even assist with driving-irrelevant tasks, such as email management and in-car infotainment [112]. Besides the obvious benefits, these IVIS functions are also distracting, and thus potentially harmful when the driver is under high load.…”
Section: Drivingmentioning
confidence: 99%
“…The recent Car2X communication technology (see Section 6.1 will allow many more functions to become available in the near future. In addition, when in-car computers have access to wireless internet, IVIS can also assist drivers in tasks that are not driving related, such as email management [112]. Besides being useful, these IVIS functions could be potentially harmful to driving safety, because they impose additional attention demand on the driver and may cause distraction.…”
Section: Introductionmentioning
confidence: 99%